Morphogenesis of Vomeronasal Organ of Pelophylax ridibundus (Amphibia, Anura) - Stepanyuk, Ya. V.; Kovtun, M. F.; Степанюк, Я. В.; Ковтун, М. Ф. (My University, 2013)
The morphogenesis of the lake frog (Pelophylax ridibundus) vomeronasal organ was studied during different ontogenesis stages. The vomeronasal organ is laid after the formation of olfactory sacs, which are lined by olfactory epithelium, and after choan formation. Vomeronasal organ anlage takes place during G24 stage of larval development, which is the result of inflection and cell redistribution of olfactory epithelium rostroventral part. Formation of the vomeronasal organ finished at the beginning of metamorphosis. Apparently, vomeronasal organ appeared in aquatic Amphibia ancestors and after their transition from aquatic to terrestrial environment it developed new adaptive functions
Морфогенез вомероназального органу Pelophylax ridibundus (Amphibia, Anura)
Keywords: Anura; olfactory system; olfactory epithelium; vomeronasal organ; vomeronasal gland